Curable resin composition
Patent Information
- Application Number
- JP2023137246
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-08-25
- Publication Date
- 2025-03-07
AI Technical Summary
【0053】 本発明によれば、硬化後の誘電特性、耐熱性、及び、接着性に優れる硬化性樹脂組成物を提供することができる。
Smart Images

Figure 2025031192000001 
Figure 2025031192000002 
Figure 2025031192000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a curable resin composition. [Background technology]
[0002] Polymerizable monomers such as epoxy compounds, which have low shrinkage and excellent adhesion, insulation, and chemical resistance, are used in many industrial products. In particular, curable resin compositions used as interlayer insulating materials for printed wiring boards and the like require dielectric properties such as low dielectric constant and low dielectric loss tangent. As curable resin compositions with such excellent dielectric properties, for example, Patent Documents 1 and 2 disclose resin compositions containing a curable resin and a compound having a specific structure as a curing agent, and Patent Document 3 discloses a resin composition containing a monofunctional epoxy resin having a biphenyl structure and a curing agent. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2017-186551 A [Patent Document 2] International Publication No. 2016 / 114286 [Patent Document 3] JP 2018-95749 A Summary of the Invention [Problem to be solved by the invention]
[0004] In order to further reduce the dielectric constant and dielectric tangent of the curable resin composition after curing, it is possible to reduce the amount of hydroxyl groups generated in the curing system. In order to reduce the amount of hydroxyl groups generated in the curing system, it is possible to use a cationic polymerization system for the curing system. However, when the curing system is a cationic polymerization system, the adhesiveness of the obtained curable resin composition is reduced, and peeling may occur on an adherend made of a metal such as copper. In addition, it is difficult for conventional curable resin compositions to achieve both heat resistance and dielectric properties after curing. An object of the present invention is to provide a curable resin composition that is excellent in dielectric properties, heat resistance, and adhesion after curing. [Means for solving the problem]
[0005] The present disclosure 1 is a curable resin composition containing a polymerizable monomer, a cationic polymerization initiator, a polymer component, and an inorganic filler, wherein the polymerizable monomer contains a compound represented by the following formula (1), and the content of the compound represented by the formula (1) in 100 parts by mass of the polymerizable monomer exceeds 50 parts by mass. The present disclosure 2 is the curable resin composition of the present disclosure 1, wherein the polymerizable monomer further includes at least one selected from the group consisting of an epoxy compound, an oxetane compound, a (meth)acrylic compound, and a vinyl ether compound other than the compound represented by the above formula (1). The present disclosure 3 is the curable resin composition according to the present disclosure 1 or 2, in which the content of the compound represented by the above formula (1) in 100 parts by mass of the above polymerizable monomer is 60 parts by mass or more. The present disclosure 4 is the curable resin composition according to the present disclosure 1, 2, or 3, wherein the polymer component contains polyimide. The present disclosure 5 is the curable resin composition according to the present disclosure 1, 2, 3, or 4, wherein the inorganic filler contains silica.
[0006] [ka]
[0007] The present invention will be described in detail below. The present inventors have investigated the use of a specific compound as a polymerizable monomer in an amount exceeding a specific amount, and have found that it is possible to obtain a curable resin composition having excellent dielectric properties, heat resistance, and adhesiveness after curing, thereby completing the present invention.
[0008] The curable resin composition of the present invention contains a polymerizable monomer. The polymerizable monomer contains a compound represented by the formula (1). By containing the compound represented by the formula (1) in an amount described below, the curable resin composition of the present invention has excellent dielectric properties, heat resistance, and adhesiveness after curing.
[0009] The polymerizable monomer may consist of only the compound represented by formula (1) above, but may also contain other polymerizable monomers other than the compound represented by formula (1) above. The content of the compound represented by the formula (1) in 100 parts by mass of the polymerizable monomer exceeds 50 parts by mass. When the content of the compound represented by the formula (1) exceeds 50 parts by mass, the curable resin composition of the present invention becomes excellent in dielectric properties, heat resistance, and adhesiveness after curing. The content of the compound represented by the formula (1) is preferably 60 parts by mass or more, more preferably 80 parts by mass or more.
[0010] When the polymerizable monomer contains the other polymerizable monomer, it is preferable that the other polymerizable monomer contains at least one selected from the group consisting of epoxy compounds other than the compound represented by formula (1) (hereinafter also referred to as "other epoxy compounds"), oxetane compounds, (meth)acrylic compounds, and vinyl ether compounds. In this specification, the term "(meth)acrylic" means acrylic or methacrylic.
[0011] Examples of the other epoxy compounds include 3,4-epoxycyclohexylmethyl(3,4-epoxy)cyclohexanecarboxylate, bisphenol A type epoxy compounds, bisphenol F type epoxy compounds, bisphenol E type epoxy compounds, phenyl glycidyl ether, phenylene diglycidyl ether, 4,4'-bis(1,2-epoxycyclohexane), bis(3,4-epoxycyclohexylmethyl)ether, bis(3,4-epoxycyclohexylmethyl)adipate, 1,2-epoxy-4-(2-oxiranyl)cyclohexane adduct of 2,2-bis(hydroxymethyl)-1-butanol, methacrylic acid ((3 ,4-epoxycyclohexane)-1-yl)methyl, fluorene type epoxy compound, 1,7-octadiene diepoxide, neopentyl glycol diglycidyl ether, ethylene glycol diglycidyl ether, diethylene glycol diglycidyl ether, polyethylene glycol diglycidyl ether, propylene glycol diglycidyl ether, dipropylene glycol diglycidyl ether, tripropylene glycol diglycidyl ether, polypropylene glycol diglycidyl ether, 1,6-hexanediol diglycidyl ether, glycerin diglycidyl ether, trimethylolpropane triglycidyl ether, etc. Among them, 3,4-epoxycyclohexylmethyl (3,4-epoxy) cyclohexane carboxylate, bisphenol A type epoxy compound, bisphenol F type epoxy compound, bisphenol E type epoxy compound, phenyl glycidyl ether are preferred, and phenyl glycidyl ether is more preferred.
[0012] Examples of the oxetane compound include 3-ethyl-3-((2-ethylhexyloxy)methyl)oxetane, 3-ethyl-3-(((3-ethyloxetan-3-yl)methoxy)methyl)oxetane, 3-ethyl-3-((3-(triethoxysilyl)propoxy)methyl)oxetane, phenol novolac oxetane, 1,4-bis(((3-ethyl-3-oxetanyl)methoxy)methyl)benzene, etc. Among them, 3-ethyl-3-((2-ethylhexyloxy)methyl)oxetane is preferred.
[0013] Examples of the (meth)acrylic compound include 1,6-hexanediol di(meth)acrylate, 1,9-nonanediol di(meth)acrylate, diethylene glycol di(meth)acrylate, triethylene glycol di(meth)acrylate, tetraethylene glycol di(meth)acrylate, dipropylene glycol di(meth)acrylate, tripropylene glycol di(meth)acrylate, tetrapropylene glycol di(meth)acrylate, polytetramethylene glycol di(meth)acrylate, 1,12-dodecanediol di(meth)acrylate, trimethylolpropane tri(meth)acrylate, neopentyl glycol di(meth)acrylate, dimethylol tricyclodecane di(meth)acrylate, (meth)acrylic modified organosiloxane, etc. Among them, 1,6-hexanediol di(meth)acrylate and 1,9-nonanediol di(meth)acrylate are preferred. In this specification, the term "(meth)acrylate" means acrylate or methacrylate.
[0014] Examples of the vinyl ether compound include dicyclopentadiene vinyl ether, benzyl vinyl ether, cyclohexanedimethanol monovinyl ether, 1,4-butanediol divinyl ether, cyclohexanedimethanol divinyl ether, diethylene glycol divinyl ether, triethylene glycol divinyl ether, dipropylene glycol divinyl ether, tripropylene glycol divinyl ether, etc. Among these, dicyclopentadiene vinyl ether is preferred.
[0015] The preferred lower limit of the content of the polymerizable monomer in 100 parts by mass of the total solid content of the curable resin composition of the present invention is 2 parts by mass, and the preferred upper limit is 32 parts by mass. By having the content of the polymerizable monomer in this range, the obtained curable resin composition has better curability and adhesiveness. The more preferred lower limit of the content of the polymerizable monomer is 2.5 parts by mass. In this specification, the above-mentioned "total solid content of the curable resin composition" means, when the curable resin composition contains a solvent described below, all components other than the solvent.
[0016] The curable resin composition of the present invention contains a cationic polymerization initiator. By making the curing system a cationic polymerization system using the cationic polymerization initiator, the curable resin composition of the present invention can reduce the amount of hydroxyl groups generated in the curing system, and has excellent dielectric properties after curing. Examples of the cationic polymerization initiator include a photo-cationic polymerization initiator and a thermal cationic polymerization initiator.
[0017] The thermal cationic polymerization initiator has an anion moiety of BF 4 - , P.F. 6 - , SbF 6 - , or (BX 4 ) -(wherein X represents a phenyl group substituted with at least two or more fluorine atoms or trifluoromethyl groups), sulfonium salts, phosphonium salts, ammonium salts, diazonium salts, iodonium salts, etc. are included. Among these, sulfonium salts are preferred.
[0018] Examples of the sulfonium salt include triphenylsulfonium tetrafluoroborate and triphenylsulfonium hexafluoroantimonate.
[0019] Examples of the phosphonium salt include ethyltriphenylphosphonium hexafluoroantimonate and tetrabutylphosphonium hexafluoroantimonate.
[0020] Examples of the ammonium salt include dimethylphenyl(4-methoxybenzyl)ammonium hexafluorophosphate, dimethylphenyl(4-methoxybenzyl)ammonium hexafluoroantimonate, dimethylphenyl(4-methoxybenzyl)ammonium tetrakis(pentafluorophenyl)borate, dimethylphenyl(4-methylbenzyl)ammonium hexafluorophosphate, dimethylphenyl(4-methylbenzyl)ammonium hexafluoroantimonate, dimethylphenyl(4-methylbenzyl)ammonium hexafluorotetrakis(pentafluorophenyl)borate, and methylphenyldibenzylammonium hexafluorophosphate. , methylphenyldibenzylammonium hexafluoroantimonate, methylphenyldibenzylammonium tetrakis(pentafluorophenyl)borate, phenyltribenzylammonium tetrakis(pentafluorophenyl)borate, dimethylphenyl(3,4-dimethylbenzyl)ammonium tetrakis(pentafluorophenyl)borate, N,N-dimethyl-N-benzylanilinium hexafluoroantimonate, N,N-diethyl-N-benzylanilinium tetrafluoroborate, N,N-dimethyl-N-benzylpyridinium hexafluoroantimonate, and N,N-diethyl-N-benzylpyridinium trifluoromethanesulfonate.
[0021] Among the above-mentioned thermal cationic polymerization initiators, examples of commercially available ones include thermal cationic polymerization initiators manufactured by Sanshin Chemical Industry Co., Ltd. and thermal cationic polymerization initiators manufactured by King Industries. Examples of the thermal cationic polymerization initiators manufactured by Sanshin Chemical Industry Co., Ltd. include San-Aid SI-60, San-Aid SI-80, San-Aid SI-B3, San-Aid SI-B3A, and San-Aid SI-B4. Examples of the thermal cationic polymerization initiators manufactured by King Industries include CXC-1612 and CXC-1821.
[0022] The photocationic polymerization initiator is not particularly limited as long as it generates a protonic acid or a Lewis acid upon irradiation with light, and may be an ionic photoacid generating type or a nonionic photoacid generating type.
[0023] The anion portion of the ionic photoacid generating cationic photopolymerization initiator may be, for example, BF 4 - , P.F. 6 - , SbF 6 - , (BX 4 ) - (wherein X represents a phenyl group substituted with at least two fluorine or trifluoromethyl groups). The anion moiety may be PF m (C n F 2n+1 ) 6-m - (wherein, m is an integer of 0 or more and 5 or less, and n is an integer of 1 or more and 6 or less). Examples of the ionic photoacid generating type photocationic polymerization initiator include aromatic sulfonium salts, aromatic iodonium salts, aromatic diazonium salts, aromatic ammonium salts, (2,4-cyclopentadiene-1-yl)((1-methylethyl)benzene)-Fe salts, and the like, each of which has the anion moiety.
[0024] Examples of the aromatic sulfonium salt include bis(4-(diphenylsulfonio)phenyl)sulfide bishexafluorophosphate, bis(4-(diphenylsulfonio)phenyl)sulfide bishexafluoroantimonate, bis(4-(diphenylsulfonio)phenyl)sulfide bistetrafluoroborate, bis(4-(diphenylsulfonio)phenyl)sulfide tetrakis(pentafluorophenyl)borate, diphenyl-4-(phenylthio)phenylsulfonium hexafluorophosphate, diphenyl-4-(phenylthio)phenylsulfonium hexafluoroantimonate, diphenyl-4-(phenylthio)phenylsulfonium tetrafluoroborate, diphenyl-4-(phenylthio)phenylsulfonium tetrakis(pentafluorophenyl)borate, and triphenylsulfonium hexafluorophosphate. Examples of the sulfonium tetrakis(pentafluorophenyl)borate include triphenylsulfonium hexafluoroantimonate, triphenylsulfonium tetrafluoroborate, triphenylsulfonium tetrakis(pentafluorophenyl)borate, bis(4-(di(4-(2-hydroxyethoxy))phenylsulfonio)phenyl)sulfide bishexafluorophosphate, bis(4-(di(4-(2-hydroxyethoxy))phenylsulfonio)phenyl)sulfide bishexafluoroantimonate, bis(4-(di(4-(2-hydroxyethoxy))phenylsulfonio)phenyl)sulfide bistetrafluoroborate, bis(4-(di(4-(2-hydroxyethoxy))phenylsulfonio)phenyl)sulfide tetrakis(pentafluorophenyl)borate, and tris(4-(4-acetylphenyl)thiophenyl)sulfonium tetrakis(pentafluorophenyl)borate.
[0025] Examples of the aromatic iodonium salt include diphenyliodonium hexafluorophosphate, diphenyliodonium hexafluoroantimonate, diphenyliodonium tetrafluoroborate, diphenyliodonium tetrakis(pentafluorophenyl)borate, bis(dodecylphenyl)iodonium hexafluorophosphate, bis(dodecylphenyl)iodonium hexafluoroantimonate, bis(dodecylphenyl)iodonium tetrafluoroborate, bis(dodecylphenyl)iodonium tetrakis(pentafluorophenyl)borate, 4-methylphenyl-4-(1-methylethyl)phenyliodonium hexafluorophosphate, 4-methylphenyl-4-(1-methylethyl)phenyliodonium hexafluoroantimonate, 4-methylphenyl-4-(1-methylethyl)phenyliodonium tetrafluoroborate, and 4-methylphenyl-4-(1-methylethyl)phenyliodonium tetrakis(pentafluorophenyl)borate.
[0026] Examples of the aromatic diazonium salt include phenyldiazonium hexafluorophosphate, phenyldiazonium hexafluoroantimonate, phenyldiazonium tetrafluoroborate, and phenyldiazonium tetrakis(pentafluorophenyl)borate.
[0027] Examples of the aromatic ammonium salt include 1-benzyl-2-cyanopyridinium hexafluorophosphate, 1-benzyl-2-cyanopyridinium hexafluoroantimonate, 1-benzyl-2-cyanopyridinium tetrafluoroborate, 1-benzyl-2-cyanopyridinium tetrakis(pentafluorophenyl)borate, 1-(naphthylmethyl)-2-cyanopyridinium hexafluorophosphate, 1-(naphthylmethyl)-2-cyanopyridinium hexafluoroantimonate, 1-(naphthylmethyl)-2-cyanopyridinium tetrafluoroborate, and 1-(naphthylmethyl)-2-cyanopyridinium tetrakis(pentafluorophenyl)borate.
[0028] Examples of the (2,4-cyclopentadiene-1-yl)((1-methylethyl)benzene)-Fe salt include (2,4-cyclopentadiene-1-yl)((1-methylethyl)benzene)-Fe(II) hexafluorophosphate, (2,4-cyclopentadiene-1-yl)((1-methylethyl)benzene)-Fe(II) hexafluoroantimonate, (2,4-cyclopentadiene-1-yl)((1-methylethyl)benzene)-Fe(II) tetrafluoroborate, and (2,4-cyclopentadiene-1-yl)((1-methylethyl)benzene)-Fe(II) tetrakis(pentafluorophenyl)borate.
[0029] Examples of the nonionic photoacid generating cationic photopolymerization initiator include nitrobenzyl esters, sulfonic acid derivatives, phosphoric acid esters, phenolsulfonic acid esters, diazonaphthoquinones, and N-hydroxyimide sulfonates.
[0030] Among the above-mentioned photocationic polymerization initiators, commercially available ones include, for example, photocationic polymerization initiators manufactured by Midori Chemical Industry Co., Ltd., photocationic polymerization initiators manufactured by Union Carbide Corporation, photocationic polymerization initiators manufactured by ADEKA Corporation, photocationic polymerization initiators manufactured by 3M Corporation, photocationic polymerization initiators manufactured by BASF Corporation, photocationic polymerization initiators manufactured by Solvay Corporation, and photocationic polymerization initiators manufactured by San-Apro Corporation. An example of the photocationic polymerization initiator manufactured by Midori Kagaku Co., Ltd. is DTS-200. Examples of the photocationic polymerization initiator manufactured by Union Carbide include UVI6990 and UVI6974. Examples of the photocationic polymerization initiator manufactured by ADEKA Corporation include SP-150 and SP-170. Examples of the photocationic polymerization initiator manufactured by 3M include FC-508 and FC-512. Examples of the cationic photopolymerization initiator manufactured by BASF include IRGACURE261 and IRGACURE290. Examples of the photocationic polymerization initiators manufactured by Solvay include PI2074. Examples of the photocationic polymerization initiators manufactured by San-Apro include CPI-100P, CPI-200K, and CPI-210S.
[0031] The content of the cationic polymerization initiator is preferably 0.5 parts by mass at the lower limit and 10 parts by mass at the upper limit with respect to 100 parts by mass of the polymerizable monomer. By the content of the cationic polymerization initiator being within this range, the obtained curable resin composition has better curability and storage stability. The more preferred lower limit of the content of the cationic polymerization initiator is 1 part by mass, and the more preferred upper limit is 5 parts by mass.
[0032] The curable resin composition of the present invention contains a polymer component. The polymer component not only serves as a film-forming component, but also improves the dielectric properties, heat resistance, and adhesiveness of the resulting curable resin composition after curing.
[0033] The number average molecular weight of the polymer component is preferably 3000 at the lower limit and 100,000 at the upper limit. When the number average molecular weight of the polymer component is within this range, the curable resin composition obtained is more excellent in workability and heat resistance after curing. The number average molecular weight of the polymer component is more preferably 5000 at the lower limit and 80,000 at the upper limit. In this specification, the number average molecular weight is a value obtained by measuring using tetrahydrofuran as a solvent by gel permeation chromatography (GPC) and converting the molecular weight into polystyrene equivalent. Examples of columns used for measuring the number average molecular weight converted into polystyrene equivalent by GPC include Shodex LF-804 (manufactured by Showa Denko KK).
[0034] Examples of the polymer component include polyimide, phenoxy resin, polyamide, polyamideimide, polymaleimide, cyanate resin, benzoxazine resin, acrylic resin, urethane resin, polyester, etc. Among them, from the viewpoint of heat resistance, polyimide, polyamide, polyamideimide, polymaleimide are preferable, and polyimide is more preferable. The above polymer components may be used alone or in combination of two or more kinds.
[0035] From the viewpoint of lowering the dielectric constant and dielectric loss tangent of the resulting curable resin composition after curing, the polyimide preferably has a structure derived from an aliphatic diamine compound, and more preferably has a structure derived from a dimer diamine.
[0036] The content of the polymer component as a solid content is preferably 4 parts by mass at the lower limit and 20 parts by mass at the upper limit relative to 100 parts by mass of the polymerizable monomer. When the content of the polymer component is within this range, the obtained curable resin composition is more excellent in coatability, dielectric properties after curing, heat resistance, and adhesiveness. The more preferred lower limit of the content of the polymer component as a solid content is 7 parts by mass, and the more preferred upper limit is 15 parts by mass.
[0037] The curable resin composition of the present invention contains an inorganic filler. By containing the inorganic filler, the curable resin composition of the present invention has excellent dielectric properties after curing.
[0038] Examples of the inorganic filler include silica, alumina, boron nitride, magnesium oxide, and boehmite. Among these, silica is preferable. The inorganic filler may be used alone or in combination of two or more kinds.
[0039] The inorganic filler has a preferred lower limit of 0.2 μm and a preferred upper limit of 5 μm in average particle size. By setting the average particle size of the inorganic filler in this range, the inorganic filler has excellent dispersibility in the curable resin composition without deteriorating the coating property, and has a more excellent effect of achieving both dielectric properties and adhesiveness after curing. The inorganic filler has a more preferred lower limit of 0.5 μm and a more preferred upper limit of 2 μm in average particle size. The average particle size of the inorganic filler can be measured by dispersing the inorganic filler in a solvent (water, organic solvent, etc.) using a particle size distribution measuring device. Examples of the particle size distribution measuring device include NICOMP 380ZLS (manufactured by PARTICLE SIZING SYSTEMS).
[0040] The content of the inorganic filler as a solid content is preferably 200 parts by mass at the lower limit and 300 parts by mass at the upper limit relative to 100 parts by mass of the polymerizable monomer. By the content of the inorganic filler being within this range, the obtained curable resin composition is more excellent in coatability, dielectric properties after curing, and adhesiveness. The more preferable lower limit of the content of the inorganic filler as a solid content is 210 parts by mass, and the more preferable upper limit is 263 parts by mass.
[0041] The curable resin composition of the present invention may contain an organic filler for the purpose of stress relaxation, imparting toughness, etc., within the scope of not impairing the object of the present invention. Examples of the organic filler include silicone rubber particles, acrylic rubber particles, urethane rubber particles, polyamide particles, polyamideimide particles, polyimide particles, benzoguanamine particles, and core-shell particles thereof. Among these, polyamide particles, polyamideimide particles, and polyimide particles are preferred. The organic filler may be used alone or in combination of two or more.
[0042] The curable resin composition of the present invention may contain a leveling agent from the viewpoint of the flatness of the coating film. Examples of the leveling agent include silicone-based leveling agents, fluorine-based leveling agents, and acrylic-based leveling agents.
[0043] The content of the leveling agent is preferably 0.1 parts by mass at the lower limit and 10 parts by mass at the upper limit with respect to 100 parts by mass of the polymerizable monomer. By the content of the leveling agent being within this range, the obtained curable resin composition has better coatability and flatness of the coating film. The more preferred lower limit of the content of the leveling agent is 0.5 parts by mass, and the more preferred upper limit is 2 parts by mass.
[0044] The curable resin composition may contain a solvent from the viewpoint of coatability and the like. From the viewpoints of coatability, storage stability, and the like, the above solvent is preferably a solvent having a boiling point of less than 200°C. Examples of the solvent having a boiling point of less than 200° C. include alcohol-based solvents, ketone-based solvents, ester-based solvents, hydrocarbon-based solvents, halogen-based solvents, ether-based solvents, and nitrogen-containing solvents. Examples of the alcohol solvent include methanol, ethanol, isopropyl alcohol, normal propyl alcohol, isobutyl alcohol, normal butyl alcohol, tertiary butyl alcohol, and 2-ethylhexanol. Examples of the ketone solvent include acetone, methyl ethyl ketone, methyl isobutyl ketone, methyl propyl ketone, diisobutyl ketone, cyclohexanone, methylcyclohexanone, and diacetone alcohol. Examples of the ester solvent include methyl acetate, ethyl acetate, butyl acetate, isobutyl acetate, methoxybutyl acetate, amyl acetate, n-propyl acetate, isopropyl acetate, methyl lactate, ethyl lactate, and butyl lactate. Examples of the hydrocarbon solvent include benzene, toluene, xylene, normal hexane, isohexane, cyclohexane, methylcyclohexane, ethylcyclohexane, isooctane, normal decane, and normal heptane. Examples of the halogen-based solvent include dichloromethane, chloroform, and trichloroethylene. Examples of the ether solvents include diethyl ether, tetrahydrofuran, 1,4-dioxane, 1,3-dioxolane, diisopropyl ether, ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, ethylene glycol monobutyl ether, ethylene glycol monotertiary butyl ether, propylene glycol monomethyl ether, propylene glycol monomethyl ether acetate, propylene glycol monomethyl ether propionate, 3-methoxybutanol, 3-methoxy-3-methyl-1-butanol, diethylene glycol dimethyl ether, anisole, and 4-methylanisole. Examples of the nitrogen-containing solvent include acetonitrile, N,N-dimethylformamide, and N,N-dimethylacetamide. Among these, from the viewpoints of handling and solubility of the curing agent, it is preferable to use at least one selected from the group consisting of ketone-based solvents having a boiling point of 60° C. or more and less than 200° C., ester-based solvents having a boiling point of 60° C. or more and less than 200° C., and ether-based solvents having a boiling point of 60° C. or more and less than 200° C. Examples of such solvents include methyl ethyl ketone, methyl isobutyl ketone, ethyl acetate, isobutyl acetate, 1,4-dioxane, 1,3-dioxolane, tetrahydrofuran, cyclohexanone, methylcyclohexanone, diethylene glycol dimethyl ether, and anisole. The above solvents may be used alone or in combination of two or more kinds. The above "boiling point" refers to a value measured under a condition of 101 kPa, or a value converted to 101 kPa using a boiling point conversion chart or the like.
[0045] The preferred lower limit of the content of the solvent in 100 parts by mass of the curable resin composition containing the solvent is 20 parts by mass, and the preferred upper limit is 90 parts by mass. By having the content of the solvent in this range, the obtained curable resin composition has better coatability and the like. The more preferred lower limit of the content of the solvent is 30 parts by mass, and the more preferred upper limit is 80 parts by mass.
[0046] The curable resin composition of the present invention may further contain additives such as a dispersant, a flame retardant, a coupling agent, a storage stabilizer, a bleed inhibitor, and a fluxing agent.
[0047] The method for producing the curable resin composition of the present invention may, for example, be a method of mixing a polymerizable monomer, a cationic polymerization initiator, a polymer component, an inorganic filler, additives such as a leveling agent, and a solvent using a mixer. Examples of the mixer include a homodisper, a universal mixer, a Banbury mixer, and a kneader.
[0048] The curable resin composition of the present invention can be applied onto a substrate film and dried to obtain a curable resin composition film made of the curable resin composition of the present invention, and the curable resin composition film can be cured to obtain a cured product.
[0049] The curable resin composition of the present invention has a preferred upper limit of the dielectric constant of the cured product at 23° C. of 2.80. Since the cured product has a dielectric constant of 2.80 or less at 23° C., the curable resin composition of the present invention can be suitably used as an interlayer insulating material for multilayer printed wiring boards, etc. The more preferred upper limit of the dielectric constant of the cured product at 23° C. is 2.75. The dielectric constant and the dielectric loss tangent described later are values measured at 1.0 GHz using a dielectric constant measuring device and a network analyzer. The cured product for measuring the dielectric constant and the dielectric loss tangent described later can be obtained by curing the above-mentioned curable resin composition film having a thickness of 40 to 200 μm. As a curing method, in the case of a thermosetting curable resin composition, a method of heating at 190° C. for 1 hour is used, and in the case of a photocurable curable resin composition, a method of irradiating ultraviolet light having a wavelength of 365 nm at 3000 mJ / cm is used. 2 In the case of a photo-curable resin composition of the photothermal curing type, the above two methods are used in combination.
[0050] The curable resin composition of the present invention preferably has a dielectric loss tangent of less than 0.0030 at 23° C. The dielectric loss tangent of the cured product at 23° C. is less than 0.0030, so that the curable resin composition of the present invention can be suitably used as an interlayer insulating material for multilayer printed wiring boards and the like. The dielectric loss tangent of the cured product at 23° C. is more preferably 0.0025 or less.
[0051] The curable resin composition of the present invention preferably has an adhesive strength of 4 N / cm or more to copper foil. Since the adhesive strength of the cured product to copper foil is 4 N / cm or more, the curable resin composition of the present invention can be suitably used as an interlayer insulating material for multilayer printed wiring boards and the like. The adhesive strength of the cured product to copper foil is more preferably 6 N / cm or more. The adhesive strength to the copper foil can be measured as the peel strength when a 90° peel test is performed on a test piece cut to a width of 1 cm at 25° C. and a peel speed of 50 mm / min using a tensile tester. The test piece can be obtained by laminating a 25 μm thick polyimide substrate on one side of a 20 μm thick curable resin composition film and a 35 μm thick copper foil on the other side, and then curing the curable resin composition film. As a curing method, in the case of a thermosetting curable resin composition, a method of heating at 190° C. for 1 hour is used, and in the case of a photocurable curable resin composition, a method of irradiating ultraviolet light having a wavelength of 365 nm at 3000 mJ / cm is used.2 A method of irradiating the film with light is used, and in the case of a photothermosetting type curable resin composition, both of these methods are used in combination. As the copper foil, Kapton 100H (manufactured by Toray DuPont Co., Ltd., 25 μmt) or the like can be used. As the copper foil, the glossy side of an electrolytic copper foil (manufactured by Fukuda Metal Foil and Powder Co., Ltd., "UN series", glossy surface roughness (Ra) 0.25 μm) can be used. As the tensile tester, for example, UCT-500 (manufactured by ORIENTEC Co., Ltd.) can be used.
[0052] The curable resin composition of the present invention can be used in a wide range of applications, such as adhesives for printed wiring boards, coverlay adhesives for flexible printed circuit boards, copper-clad laminates, semiconductor bonding adhesives, interlayer insulating materials, prepregs, LED sealants, and adhesives for structural materials. In particular, the curable resin composition of the present invention can be suitably used as an interlayer insulating material for multilayer printed wiring boards and the like, since the cured product has a low dielectric constant, a low dielectric loss tangent, and excellent dielectric properties. Effect of the Invention
[0053] According to the present invention, it is possible to provide a curable resin composition that is excellent in dielectric properties, heat resistance, and adhesion after curing. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0054] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples.
[0055] (Preparation of compound represented by formula (2)) In a 200 mL four-neck flask equipped with a stirrer, a thermometer, and a condenser, 6.4 g of 1,2-epoxy-4-vinylcyclohexane, 0.05 g of a 2 mass% ethanol solution of hexachloroplatinic acid hexahydrate, and 100 g of toluene were added under a nitrogen atmosphere, and the liquid temperature was raised to 70° C. Then, 5.0 g of 1,4-bis(dimethylsilyl)benzene was added dropwise over 15 minutes, and the mixture was stirred at 90° C. for 4 hours. The toluene was removed by concentration under reduced pressure, and a compound represented by the following formula (2) was obtained.
[0056] [ka]
[0057] (Preparation of polyimide resin solution) 54.6 parts by mass of 4,4'-(4,4'-isopropylidenediphenoxy)diphthalic anhydride (manufactured by Tokyo Chemical Industry Co., Ltd.) and 200 parts by mass of cyclohexanone were charged and dissolved in a reaction vessel equipped with a stirrer, a water divider, and a nitrogen gas inlet tube. A mixed solution of 56.1 parts by mass of Priamine 1074 (manufactured by Croda) which is a dimer diamine and 55.0 parts by mass of cyclohexanone was dropped into the obtained solution, and then an imidization reaction was carried out at 150°C for 8 hours to obtain a polyimide resin solution. The solid content concentration of the obtained polyimide resin solution was 30% by mass, and the number average molecular weight of the polyimide resin was 25,000.
[0058] (Examples 1 to 16, Comparative Examples 1 to 10) According to the compounding ratios shown in Tables 1 to 3, the materials were mixed by stirring to prepare the curable resin compositions of Examples 1 to 16 and Comparative Examples 1 to 10.
[0059] <Evaluation> The following evaluations were performed on each of the curable resin compositions obtained in the Examples and Comparative Examples. The results are shown in Tables 1 to 3. The following evaluations were not performed on the curable resin composition obtained in Comparative Example 8 because the cured product became brittle, and the following evaluations were not performed on the curable resin composition obtained in Comparative Example 10 because it could not be sufficiently cured even when heated at 190°C for 1 hour.
[0060] (Dielectric properties) Each of the obtained curable resin compositions was applied onto a substrate PET film and dried to obtain an uncured laminate film having a substrate PET film and a curable resin composition layer having a thickness of 40 μm on the substrate PET film. The obtained uncured laminate film was cut into a size of 2 mm in width and 80 mm in length. The substrate PET film was peeled off from the curable resin composition layer of the cut uncured laminate film, and five curable resin composition layers were laminated using a laminator to obtain a laminate having a thickness of about 200 μm. The obtained laminate was cured to obtain a cured product. The laminates using the curable resin compositions obtained in Examples 1 to 10, 12 to 16, and Comparative Examples 1 to 7 and 9 were heated at 190° C. for 1 hour to be cured. The laminate using the curable resin composition obtained in Example 11 was cured by irradiating 3000 mJ / cm 2 of ultraviolet light having a wavelength of 365 nm using an LED UV lamp. 2 The dielectric constant and dielectric loss tangent of the obtained cured product were measured at 23° C. and a frequency of 1.0 GHz by the cavity resonance method using a cavity resonance perturbation method dielectric constant measuring device CP521 (manufactured by Kanto Electronics Application Development Co., Ltd.) and a network analyzer N5224A PNA (manufactured by Keysight Technologies, Inc.). The dielectric properties (dielectric constant) were evaluated according to the following criteria. ◎: When the relative dielectric constant is 2.75 or less ○: When the relative dielectric constant is more than 2.75 and is 2.80 or less △: When the relative dielectric constant is greater than 2.80 and less than 3.00 ×: The relative dielectric constant was 3.00 or more. In addition, the dielectric properties (dielectric tangent) were evaluated according to the following criteria. ◎: When the dielectric tangent is 0.0025 or less ○: When the dielectric tangent is greater than 0.0025 and less than 0.0030 △: When the dielectric tangent is 0.0030 or more and less than 0.0040 ×: When the dielectric tangent is 0.0040 or more
[0061] (heat resistance) Each of the obtained curable resin compositions was applied to a polyimide substrate (Toray DuPont Co., Ltd., "Kapton 100H", thickness 25 μm) to a thickness of about 20 μm, and dried to obtain a laminate having a curable resin composition film on a polyimide substrate. The obtained laminate was cut to a width of 1 cm, and a copper foil having a thickness of 35 μm (the shiny surface of electrolytic copper foil, "CF-T8G-UN-35", manufactured by Fukuda Metal Foil and Powder Co., Ltd.) was laminated on the curable resin composition side, and the curable resin composition layer was cured to obtain a test piece. The laminates using the curable resin compositions obtained in Examples 1 to 10, 12 to 16, and Comparative Examples 1 to 7 and 9 were cured by hot pressing under conditions of 190°C, 3 MPa, and 1 hour. The laminate using the curable resin composition obtained in Example 11 was cured by applying ultraviolet light of 365 nm wavelength at 3000 mJ / cm using an LED UV lamp. 2 The obtained test pieces were left in an environment of 40°C and 90% RH for 96 hours, and then a reflow test was performed in which the test pieces were heated at 260°C for 20 seconds. After the reflow test, 10 test pieces were visually inspected for swelling. The heat resistance was evaluated according to the following criteria. ◎: No blister was observed in any of the test pieces ○: Blistering was confirmed in one test piece △: Blisters were observed in two test pieces ×: Blisters were found in three or more test pieces.
[0062] (Adhesion to copper foil) Each of the obtained curable resin compositions was applied to a polyimide substrate (Toray DuPont Co., Ltd., "Kapton 100H", thickness 25 μm) to a thickness of about 20 μm, and dried to obtain a laminate having a curable resin composition film on a polyimide substrate. The obtained laminate was cut to a width of 1 cm, and a copper foil having a thickness of 35 μm (the shiny surface of electrolytic copper foil, "CF-T8G-UN-35", manufactured by Fukuda Metal Foil and Powder Co., Ltd.) was laminated on the curable resin composition side, and the curable resin composition layer was cured to obtain a test piece. The laminates using the curable resin compositions obtained in Examples 1 to 10, 12 to 16, and Comparative Examples 1 to 7 and 9 were cured by hot pressing under conditions of 190°C, 3 MPa, and 1 hour. The laminate using the curable resin composition obtained in Example 11 was cured by applying ultraviolet light of 365 nm wavelength at 3000 mJ / cm using an LED UV lamp. 2 The test pieces were cured by irradiating the film with light. The peel strength was measured by a 90° peel test at a peel speed of 50 mm / min at 25° C. using a tensile tester (manufactured by ORIENTEC Corporation, “UCT-500”) within 24 hours after preparation. The adhesion to the copper foil was evaluated according to the following criteria. ◎: Peel strength is 6N / cm or more ○: Peel strength is 4N / cm or more and less than 6N / cm △: Peel strength is 3N / cm or more and less than 4N / cm ×: Peel strength was less than 3N / cm
[0063] [Table 1]
[0064] [Table 2]
[0065] [Table 3] [Industrial Applicability]
[0066] According to the present invention, it is possible to provide a curable resin composition that is excellent in dielectric properties, heat resistance, and adhesion after curing.
Claims
1. The composition contains a polymerizable monomer, a cationic polymerization initiator, a polymer component, and an inorganic filler, The polymerizable monomer includes a compound represented by the following formula (1): The content of the compound represented by the formula (1) in 100 parts by mass of the polymerizable monomer is more than 50 parts by mass. A curable resin composition comprising: 【Chemistry 1】
2. The curable resin composition according to claim 1, wherein the polymerizable monomer further comprises at least one selected from the group consisting of an epoxy compound other than the compound represented by formula (1), an oxetane compound, a (meth)acrylic compound, and a vinyl ether compound.
3. 3. The curable resin composition according to claim 1, wherein the content of the compound represented by formula (1) is 60 parts by mass or more based on 100 parts by mass of the polymerizable monomer.
4. The curable resin composition according to claim 1 , wherein the polymer component comprises a polyimide.
5. The curable resin composition according to claim 1 , wherein the inorganic filler comprises silica.
Citation Information
Patent Citations
Polyimide, polyimide-based adhesive, film-like adhesive material, adhesive layer, adhesive sheet, copper foil with resin, copper-clad laminate and printed wiring board, and multilayer wiring board and method for manufacturing the same
JP2017186551A
Resin composition
JP2018095749A
Resin composition, support with resin layer, prepreg, laminate, multilayered printed wiring board, and printed wiring board for millimeter-wave radar
WO2016114286A1